ENGLISH SPEAKING COUNTRIES - Abdumoʻminova Sojida; Zoirova Lola; Mardonova Marjona (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: English is one of the most widely spoken languages in the world and is used as an official or second language in many countries. The spread of English is related  to  historical,  cultural  and  economic  factors.  This  article  provides  detailed information about English-speaking countries, their history, culture, and the role of the English language.